HUBUNGAN PENGGUNAAN HAND SANITIZER DENGAN TERJADINYA DERMATITIS KONTAK IRITAN PADA MAHASISWA FK UISU MASA COVID-19: CORRELATION USE OF HAND SANITIZERS WITH OCCURRENCE OF IRRITANT CONTACT DERMATITIS FK UISU DURING COVID-19 - Della, Zahra; Harris, Bilkes (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2025)
Background: Irritant contact dermatitis is an inflammatory condition of the skin due to eUISUposure to irritants. According to the Centers for Disese Control and Prevention (CDC), prevention of COVID-19 can be done by maintaining hand hygiene by using a hand sanitizer. Objective: Correlation Use Of Hand Sanitizers With Occurrence Of Irritant Contact Dermatitis FK UISU During Covid-19. Method: Observational analytic research with a cross-sectional approach with a consecutive sampling technique. The sample size is 181 students of the Faculty of Medicine, Islamic University of North Sumatra class of 2019, 2020, and 2021. Data was collected using a questionnaire which was distributed directly to the respondents. Hypothesis testing using univariate and bivariate analysis. Results: The results of statistical analysis using the contingency coefficient test found that there is no significant relationship between the use of hand sanitizer and the occurrence of irritant contact dermatitis (p=0.556) in students of the Faculty of Medicine, Islamic University of North Sumatra during the COVID-19 pandemic. Conclusion: There is no significant relationship between the use of hand sanitizers and the occurrence of irritant contact dermatitis in students of the Faculty of Medicine, Islamic University of North Sumatra during the COVID-19 pandemic AbstrakLatar Belakang: Dermatitis kontak iritan adalah suatu keadaan peradangan pada kulit akibat paparan zat iritan. Menurut Centers for Disease Control and Prevention (CDC), pencegahan COVID-19 dapat dilakukan dengan menjaga kebersihan tangan dengan menggunakan hand sanitizer. Namun penggunaan hand sanitizer yang tidak tepat dapat menyebabkan terjadinya dermatitis kontak iritan. Tujuan: Mengetahui hubungan penggunaan hand sanitizer dengan terjadinya dermatitis kontak iritan pada mahasiswa Fakultas Kedokteran UISU di masa pandemi COVID-19. Metode: Penelitian analitik observasional dengan pendekatan cross-sectional dan teknik consecutive sampling. Besar sampel adalah 181 orang mahasiswa FK UISU angkatan 2019, 2020, dan 2021. Data dikumpulkan menggunakan kuesioner yang dibagikan secara langsung pada responden. Pengujian hipotesis menggunakan analisis univariat dan bivariat. Hasil: Hasil analisis data statistik dilakukan dengan uji koefisien kontingensi yang menyatakan bahwa tidak terdapat hubungan yang signifikan antara penggunaan hand santizer dengan terjadinya dermatitis kontak iritan (p=0,556) pada Mahasiswa Fakultas Kedokteran UISU di masa pandemi COVID-19. Kesimpulan: Tidak terdapat hubungan yang signifikan antara penggunaan hand sanitizer dengan terjadinya dermatitis kontak iritan pada mahasiswa Fakultas Kedokteran UISU di masa pandemi COVID-19.